Criminal Intelligence and the Privacy of Human Life - Gutauskas, Aurelijus (Teisė, 2019)
The article analyzes the problematic aspects of applicating the provisions of the Criminal Intelligence Act to the disclosure criminal offences. The author goes deeper into how much of the means used by criminal intelligence can legitimately penetrate into the private life of citizens. The examples of the case law are used as an attempt to find a limit (proportionality) between personal freedom and security in applying criminal intelligence activities.
Keywords: Criminal Intelligence; European Court of Human Rights; Supreme Court of Lithuania; proportionality